Illumination-Adapted Transceiver Design for Quadrichromatic Light-Emitting Diode Based Visible Light Communication - Jun-Ming Dong; Yi-Jun Zhu; Yan-Yu Zhang; Zheng-Guo Sun (IEEE Photonics Journal, 2018)
With the development of lighting industry and visible light communication (VLC) technology, multicolor light-emitting diode (LED) has been advised to replace phosphor-converted LED because of its higher modulation bandwidth and better lighting quality. In this paper, we developed an illumination-adapted transceiver design for a quadrichromatic LED based multicolor multiple-input multiple-output VLC system. The multicolor crosstalk caused by spectral overlapping is considered to make the channel model more realistic. The optimization problem of transceiver design is formulated to minimize total mean-square error between transmitted and received signals with the constraints of chromaticity, luminance, and signal range. Since the optimization problem is nonconvex, we develop an iterative algorithm that updates optimization variables to get the optimal transceiver and color mix ratio in the specified color temperature (CT). Simulation results indicate that the proposed method outperforms the existing design methods with the consideration of the crosstalk and has a better system performance with larger CT value.